Description of Psychological Well-Being of Early Adolescents of Santri During The Covid-19 Pandemic - Ismawati, Ismawati (International Conference on Sustainable Health Promotion, 2021)
The purpose of this study was to describe the psychological well-being of early adolescent students in Islamic boarding schools during the COVID-19 pandemic. This research was conducted in one of the Islamic boarding schools X in the city of Pamek asan, Madura, East Java. The method used in this research is descriptive qualitative method, using interviews, observation and documentation of data collection techniques. From the data generated, it is found that early adolescent students get life satisfaction in which almost all dimensions of psychological well-being are met as a whole. Although there are still some things that sometimes make students disturbed by various new regulations from pesantren regarding the effects of the spread of the COVID-19 pandemic, so it takes time to adjust